The effect of asthma controlling on heart rate recovery in patients with asthma - Cuglan, Bilal; Bagci, Belma Akbaba; Altintas, Mehmet Sait; Altuntas, Emine (Annals of Medical Research, 2022)
Aim: The heart rate recovery index (HRRI) impairment was found in patients with pulmonary disease such as obstructive sleep apnea syndrome. Asthma is one of the most prevalent respiratory diseases in worldwide. In this study, we aimed to investigate the presence of HRRI impairment with asthma control test in patients with asthma. Material and Methods: A total of 45 people with asthma and 47 healthy participants were consequently enrolled to study from December 2019 through March 2020. The Asthma Control Test™(ACT) survey was used to evaluate the status of asthma. All participants were to undergo cardiopulmonary exercise testing. Heart rate recovery was calculated according to heart rate decreasing in recovery period. Results: Two groups had similar results in terms of laboratory parameters and demographic features. There was a statistically difference in exercise capacity, peak exercise heart rate, (METs) and duration of exercise. Also, all HRRI parameters were reached statistically significant when compared with control group. However, there was no statistically significance in HRRI when ACT groups were compared with each other. Conclusions: The differences of HRRI in ACT groups did not reach to statistically significance. This result could be a consequence of having only two ACT groups and not having any patients belonging to the well-controlled group.
Keywords: Heart rate recovery index; asthma; asthma control test; cardiovascular mortality